(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2026)
Systemic connective tissue diseases (SCTDs) represent a heterogeneous group of chronic, often progressive, autoimmune disorders characterized by the involvement of collagen and elastin-containing tissues. Among the most common SCTDs are systemic lupus erythematosus, systemic sclerosis, polymyositis, dermatomyositis, Sjögren’s syndrome, and rheumatoid arthritis. These conditions can affect almost any organ system, but one of their most significant and life-threatening complications is cardiac involvement. Understanding the clinical and pathogenetic aspects of heart damage in the context of systemic connective tissue diseases is essential for improving prognosis, management strategies, and patient survival.